The Effectiveness of Combination of Local Point Acupuncture Therapy with Topical Clove Oil (Syzygium aromaticum) Method on Pain Scale in Knee Pain Patients in Ngrambe Village, Ngawi Regency - Abdillah, Fajar Annas; Sumanto; Nugraha, Nurtama Aditya (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
Knee pain is a disorder that affects the articular cartilage, subchondral bone, synovium, joint capsule, and ligaments. The prognosis for knee pain can be good if the disease can be found in the early stages of damage. Until now, no cure has been found that can definitely cure knee pain and this disease often causes interference in daily activities. This research uses a quantitative type of research with a Quasi-Experimental research design with a two groups pre and post-test design. To measure the degree of pain, knee pain was measured using the NRS (Numeric Rating Scale). The total sample was 36 sufferers according to the inclusion and exclusion criteria in Ngrambe Village, Ngawi Regency. Then treated with a combination of herbal clove oil (Syzygium aromaticum) and local point acupuncture therapy. Combination therapy of clove oil (Syzygium aromaticum) with acupuncture is effective in reducing the scale of knee pain in Ngrambe Village, Ngawi Regency.